Marketing orientation, strategic orientation and their synergistic impact on business performance: a case of SMEs in emerging context (India). Issue 1 (11th July 2016) - Chahal, Hardeep; Dangwal, R C; Raina, Swati
Abstract : Purpose: The main purpose of the study is to examine the synergistic impact of marketing and strategic orientation on business performance and to explore role of entrepreneurial qualification (moderating) and strategic orientation (mediating) in marketing orientation and business performance relationship. Design/methodology/approach: 900 SMEs owners/managers operating in Jammu District, North India, are contacted during October, 2013 to February, 2014. Findings: The study identifies and confirms marketing orientation (marketing strategy, customer philosophy, operational efficiency and integrated marketing) and strategic orientation (defensive, proactive, analytical and risk-averse) as multi-dimensional constructs. Although both orientations have positive impact on SMEs performance, however their synergistic impact is weak. In addition, the study also reveals that marketing orientation has direct and indirect impact (through SO) on business performance. Lastly, there exists moderating role of entrepreneurial qualification between marketing and strategic orientation. Research limitations/implications: The major limitation of the study is the focus on SMEs. Based on the strength of the relationships among the dimensions and sub-dimensions of the marketing orientation, strategic orientation and business performance, replication and validation of research in service sector across country and globe is required to generalise the results and to develop stronger theory. Originality/value: This is the first empirical study to investigate the synergistic impact of two well established notions, marketing orientation and strategic orientation. It provides empirical evidence for the claim that synergistic impact of marketing and strategic orientations on business performance is weak unlike their respective strong impact on business performance. This study also clarifies roles of entrepreneurial qualification and strategic orientation in marketing orientation and business performance relationship.